PHOTOCURRENT ENHANCEMENT OF CdS QUANTUM DOT SENSITIZED TiO2 ELECTRODE IN THE PRESENCE OF GOLD NANO PARTICLES - Supriyono Supriyono; Hedi Surahman; Yuni Krisyuningsih Krisnandi; Jarnuzi Gunlazuardi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
PHOTOCURRENT ENHANCEMENT OF CdS QUANTUM DOT SENSITIZED TiO2 ELECTRODE IN THE PRESENCE OF GOLD NANO PARTICLES. Photo current enhancement of CdS Quantum Dot (CdS-QD) sensitized TiO2 electrode in the presence of gold nano particles had been investigated. CdS quantum dots were prepared by successive ionic layer adsorption and reaction (SILAR) method, in which solution containing Cd(CH3COO)2 and Na2S were used as a precursor. Where as, gold nano particles was synthesized using solution containing HAuCl4 as a precursor, NaBH4 as a reducing agent and polyvinyl pyrrolydone (PVP) as a stabilizer. The film of CdS quantum dots and Au nano particles were characterized by UV-Vis spectrophotometer, Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD), and electro chemical working station. Photo electrochemical study revealed that CdS-sensitized TiO2 electrode with gold nanoparticles have been able to increase photocurrent of 54 A/cm2 to 68 A/cm2, so the photocurrent enhancement of approximately 25% was observed. This observation indicates that the gold nanoparticles is potentially applicable to enhance photocurrent in a CdS-QD sensitized TiO2 electrode, which may lead to the development of more efficient solar cell.